Driving over the hill: Car intensity during structural transformation - Ciaráan Mac Domhnaill (University College Dublin, UCD School of Economics, 2024)
This paper examines the number of licensed private cars in the economy per unit of GDP, or car intensity, as an intrinsic component of car use that may be underlying the observed peak car phenomenon. Using data on 88 countries from 1950 to 2010, I demonstrate that car intensity evolves in a hump-shaped pattern during economic development. I develop a general equilibrium model to argue that structural transformation can generate this trend. My calibrated model can account for just under a quarter of observed variation in car intensity among 54 countries in 2010. Counterfactual exercises show that the peak level of intensity is lower for economies that develop later
Keywords: O41; N10; O18; R10; 330; peak car; structural transformation; economic growth; economic development; industrialisation; transport